2021
DOI: 10.1038/s41598-021-92885-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers in pregnant women with COVID-19: a retrospective cohort study

Abstract: Coronavirus disease 2019 (COVID-19) is a pandemic viral disease affecting also obstetric patients and uncertainties exist about the prognostic role of inflammatory biomarkers and hemocytometry values in patients with this infection. To clarify that, we have assessed the values of several inflammatory biomarkers and hemocytometry variables in a cohort of obstetric patients hospitalized with COVID-19 and we have correlated the values at admission with the need of oxygen supplementation during the hospitalization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…CRP can be used to monitor the evolution of COVID-19 disease. Study by Lombardi et al 18 concluded that CRP was related with severity of disease or mortality. As the 116-amino acid precursor of calcitonin hormone, PCT can be synthesized in many extra thyroid tissues during bacterial infection, which is mediated by increased concentrations of tumor necrosis factor alpha (TNF-a) and interleukin (IL)-6.…”
Section: Discussionmentioning
confidence: 99%
“…CRP can be used to monitor the evolution of COVID-19 disease. Study by Lombardi et al 18 concluded that CRP was related with severity of disease or mortality. As the 116-amino acid precursor of calcitonin hormone, PCT can be synthesized in many extra thyroid tissues during bacterial infection, which is mediated by increased concentrations of tumor necrosis factor alpha (TNF-a) and interleukin (IL)-6.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal infection and inflammation associated with COVID-19 could prompt potential pregnancy complications through this “cytokine storm”. Several studies reported increased expression of inflammatory biomarkers in pregnant women with COVID-19 ( 21 , 30 , 43 ). Thus, we assessed the impact of SARS-CoV-2 infection during pregnancy on placental inflammation as a potential cause of adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While evaluating the laboratory profile we observed significantly raised NLR (p=0.002), CRP (p<0.001), D-Dimer (p=0.002) and abnormal chest X-ray findings (p<0.001) in CW2 obstetrical patients. Lombardi et al also noted raised median values of NLR, CRP and D-dimer (4.4, 1.66 mg/dL and 1,727 μg/L, respectively) [ 11 ]. The umbrella review by A Ciapponii including 66 systematic reviews of observational studies related to COVID-19 in pregnancy reported raised CRP in 28%-96%, lymphocytopenia 33.6% to 80% and abnormal radiological findings in 7.1% to 99% cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that for every 1,000 lymphocyte cells decrease, the risk for oxygen supplementation increases by 26%. Since there is a physiological rise in D-dimer and a fall in serum Ferritin levels during pregnancy, they questioned their prognostic role and inferred that compared to D-dimer and ferritin, CRP is a reliable predictor for obstetrical outcome [ 11 ]. Bernard et al again observed a positive association of CRP with mortality (HR 1.002, 95% CI 1.001-0.004, p 0.0064) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%